Structure change of monoclinic ZrO2 baddeleyite involving softenings of bulk modulus and atom vibrations. Issue 4 (9th August 2019) - Fukui, Hiroshi; Fujimoto, Manato; Akahama, Yuichi; Sano-Furukawa, Asami; Hattori, Takanori
Abstract : Deformation of a sublattice composed of O atoms is related to compressional anomalies of baddeleyite: softenings of bulk modulus and atom vibrations. Abstract : Monoclinic ZrO2 baddeleyite exhibits anomalous softenings of the bulk modulus and atom vibrations with compression. The pressure evolution of the structure is investigated using neutron powder diffraction combined with ab initio calculations. The results show that the anomalous pressure response of the bulk modulus is related not to the change in the bonding characters but to the deformation of an oxygen sublattice, especially one of the layers made of oxygen atoms in the crystallographic a * plane. The layer consists of two parallelograms; one is rotated with little distortion and the other is distorted with increasing pressure. The deformation of this layer lengthens one of the Zr—O distances, resulting in the softening of some atom vibrational modes.